Prevalence and Influencing Factors of Metabolic Syndrome Among Persons with Physical Disabilities - Jeonghee Jeong, RN, PhD; Jungok Yu, RN, PhD (Elsevier, 2018)
Purpose: Metabolic syndrome is an important cluster of coronary heart disease risk factors. However, it remains unclear to what extent metabolic syndrome is associated with demographic and potentially modifiable lifestyle factors among Korean persons with physical disabilities. This study aimed to determine the prevalence and influencing factors of metabolic syndrome among persons with physical disabilities using the Korean National Health Insurance Service-National Sample Cohort. Methods: The Adult Treatment Panel III criteria were used to define metabolic syndrome influencing factors and prevalence, which were evaluated in a representative sample from the 2013 Korean National Health Insurance Service-National Sample Cohort database. Characteristics were compared based on frequency using the χ2 test. The associations between metabolic syndrome and its risk factors were estimated using logistic multivariable regression analysis. Results: Metabolic syndrome was detected in 31.5% of the surveyed persons with physical disabilities. Female sex, age of ≥65 years, smoking, greater alcohol consumption, physical inactivity, higher body mass index, and a family history of diabetes were associated with increased risks of metabolic syndrome. Conclusion: The major risk factors for metabolic syndrome among persons with physical disabilities were obesity and older age. Performing physical activity was associated with a lower risk of metabolic syndrome. Therefore, we recommend using a continuous obesity management program and physical activity to prevent metabolic syndrome among persons with physical disabilities. Keywords: disabled persons, metabolic syndrome X, physical activity, obesity